Clinical features of patients with hemolytic anemia due to red blood cells membrane defect - Pustika Amalia W; Djajadiman Gatot; Teny Tjitrasari; Iswari Setianingsih; Nanis Sacharis Marzuki (Paediatrica Indonesiana, 2006)
Background Hemolytic anemia may result from corpuscular orextracorpuscular abnormalities. One of the types of corpuscularabnormalities is membrane defect. The diagnosis is sometimesdifficult and it may need special hematologic investigations. Thereare no data yet on the clinical features of red blood cell membranedefect in Cipto Mangunkusumo Hospital.Objective To evaluate the clinical features and laboratory find-ings of patients with hemolytic anemia due to red blood cells mem-brane defect in Cipto Mangunkusumo Hospital.Methods This was a descriptive study on patients with red bloodcells membrane defect who came to the Thalassemia Center atCipto Mangunkusumo Hospital during 2002-2004.Results In 2002-2004, there were 241 new cases of hemolyticanemia consisted of 116 patients with beta-thalassemia, 109 withHbE-beta thalassemia, 3 with alpha-thalassemia, and 13 with redblood cells membrane defect. The red cells membrane defect pa-tients consisted of 4 males and 9 females, ranging in age from 1months to 14 years. All subjects came to the hospital due to pale-ness as a chief compaint. Hepato-splenomegaly was found in 5 of13 cases. Laboratory findings revealed hemoglobin level 6.4-13.1g/dl (mean 9.4+2.1 g/dl), MCV 58.4-94.5 fl (mean 81.2+10.2 fl),MCHC 31.7-35.8 g/dl (mean 33.9+1.1g/dl), RDW 15.8-28.4%(mean 20.1+3.6%) and normal hemoglobin electrophoresis. Pe-ripheral blood smear showed anisocytosis, poikilocytosis,spherocytes, ovalocytes, stomatocytes, target cells, and fragmentedcells. The most common diagnosis in this group was SoutheastAsian Ovalocytosis (5/13).Conclusions In facing hemolytic anemia with normal Hb electro-phoresis or normal RBC enzyme level, the possibility of red cellsmembrane defect should be taken into consideration as a causeof this disorder. The clinical features and laboratory findings of redblood cells membrane defect patients are highly variable. Occa-sionally, hematologic investigations are necessary